Evaluation of the physical-functional resilience of Isfahan City center using spatial statistics methods and ELECTRE* - Ahmad Rahimi Juneghani; Homayoon Nooraie (Geo-spatial Information Science)
Human populations and social wealth are generally concentrated in urban areas-which may be vulnerable to natural or anthropic disasters. In recent decades, increase in the number of natural disasters has caused much economic damage and human loss. Therefore, special attention is needed to reduce vulnerability and increase the capacity and adaptability of urban systems by way of urban resilience in order to deal with natural disasters. The city of Isfahan, located in Iran, is a city with a long history. Isfahan’s location in a low-risk zone has led researchers and urban managers to believe that earthquakes will probably never occur in this city, while recent geological findings have proven the opposite. Therefore, for the first time, this study seeks to determine the physical-functional resilience in the center of Isfahan in terms of enduring a hypothetical earthquake. To achieve this goal, first the required information was collected using library and field methods and then it was analyzed by spatial statistical methods in ArcGIS software, as well as the Analytic Hierarchy Process (AHP) and the ELECTRE Multi Criteria Decision Making method. Based on the results of this study, it seems necessary to propose a special focus on increasing the physical-functional resilience of Naghsh-e Jahan, Khalja, and Shahshahan neighborhoods out of the 25 neighborhoods located in the central districts of Isfahan. Accordingly, the study can help urban science researchers, investors, city managers and local and national organizations to identify resilience districts and focus on addressing their major weaknesses, thus preventing the loss of humn, financial and various limited urban resources as a result of earthquake through increasing the resilience of the physical-functional system of the city.